Perencanaan Sistem Penyalur Petir Eksternal Pada Gedung SMK Sultan Agung 1 Tebuireng Jombang - Medika, Aditya Surya; Slamet, Puji; Widagdo, Reza Sarwo (Jurnal Teknik Informatika dan Elektro, 2023)
Lightning is a natural phenomenon that can damage buildings. There is a solution to dealing with damage from lightning strikes, namely by installing lightning protection. Lightning protection consists of termination rods, distribution cables and earthing, from the results of analysis and calculations at the Sultan Agung 1 Tebuireng Vocational High School building, Jombang requires a total 11 termination rods, 2 distribution cables for each building and 2 rods planted 3 meters deep with a distance of 15 meters so that the grounding value is below 5 ohms